Blood DNA methylation as a potential biomarker of dementia: A systematic review. Issue 1 (8th November 2017) - Fransquet, Peter D.; Lacaze, Paul; Saffery, Richard; McNeil, John; Woods, Robyn; Ryan, Joanne
Abstract: Dementia is a major public health issue with rising prevalence rates, but many individuals remain undiagnosed. Accurate and timely diagnosis is key for the optimal targeting of interventions. A noninvasive, easily measurable peripheral biomarker would have greatest utility in population‐wide diagnostic screening. Epigenetics, including DNA methylation, is implicated in dementia; however, it is unclear whether epigenetic changes can be detected in peripheral tissue. This study aimed to systematically review the evidence for an association between dementia and peripheral DNA methylation. Forty‐eight studies that measured DNA methylation in peripheral blood were identified, and 67% reported significant associations with dementia. However, most studies were underpowered and limited by their case‐control design. We emphasize the need for future longitudinal studies on large well‐characterized populations, measuring epigenetic patterns in asymptomatic individuals. A biomarker detectable in the preclinical stages of the disease would have the greatest utility in future intervention and treatment trials. Highlights: Forty‐eight manuscripts investigating peripheral DNA methylation in dementia were included. Most have been small cross‐sectional studies, and findings have been mixed. Longitudinal studies of individuals before dementia diagnosis are needed. Preclinical biomarkers have the greatest clinical utility enabling early diagnosis. Continual advances in epigenetic technologies will ensure new discoveries.